The struggle for land and justice in Kenya - Manji, Ambreena S. (2020)
Explores the limits of law in changing unequal land relations in Kenya.
Introduction: What We Talk About When We Talk About Land -- Land Reform in Kenya: The History of an Idea -- Making Mischief: Land in Modern Kenya -- Land and Constitutional Change -- The New Institutional Framework for Land Governance -- Land Governance Before the Supreme Court -- Rethinking Historical Land Injustices -- Taking Justice Seriously.
Includes bibliographical references (pages 170-196) and index.
Keywords: Land tenure -- Law and legislation -- Kenya; Land reform -- Kenya